Application of Scramble-Type Cooperative Learning Model To Improve Learning Outcomes of Class VIII B Junior High School 3 Lamongan - Chuzaimah, Siti (Science Education and Application Journal, 2024)
This study aims to improve the learning outcomes of students in class VIII-B SMP Negeri 3 Lamongan by applying the Scramble type Cooperative Learning Model. This type of research is Classroom Action Research. The material used is the respiratory system in humans in science lessons. The research subjects consisted of 1 class, namely class VIII-B as many as 28 students. This research was conducted with 2 cycles, each cycle will consist of 3 meetings. The success of improving student learning outcomes is measured through an increase in student scores from working on test questions. Student learning outcomes in the pre-cycle showed an average student score of 62.32, and after the action the average student score was 66.78 in cycle I and 80.75 in cycle II. Based on the results of the study, it can be concluded that the application of the Scramble Learning Model can improve student learning outcomes.